Analisis Penafsiran Firanda Andirja tentang Tauhid dan Tarbiyah - Yurisa, Bobi (STKIP PGRI SITUBONDO, 2024)
: The aim of this research is to carry out Firanda Andirja's interpretation of the Tauhid verses in Tafsir Juz'Amma. This research is library research, which is a type of research that limits its activities only to library collection materials and document studies without the need for field research. The research method is a character research model. This study uses data collection techniques related to tawhid verses in the interpretation of Firanda Andirja, namely the book of tafsir which is a primary source. The method used in analyzing data is the analytical descriptive method, which describes the data that has been collected, then elaborated to find answers that can approach the problem raised, dissected fundamentally, before being implemented into an idea to get a conclusion on how Firanda Andirja interprets the verses of tawhid in his tafsir. After it is clear that Firanda Andirja's interpretation of the verses of tawhid is drawn and conclusions are drawn, the process of drawing this conclusion is carried out deductively. The use of deductive methods is carried out to make explicit conclusions from general problems. The result of the research is to find the mufasir's understanding of the verses of tawhid in Tafsir Juz 'Amma. Among them affirmed the trilogy of tawhid (ar-rububiyah, al-uluhiyyah, and asma' wa shifat), distinguishing the words Rabb and Ilah. Looking at the sources used by the mufasir in interpreting the verses of tawhid in Tafsir Juz 'Amma. These sources are bi al-Ma'tsur (Narration), among them sources from the Qur'an, hadith, sayings of the companions, tabi'in, earlier books. And the source of interpretation of bi al-ra'yi (ijtihadi). Discover the efforts made by the mufasir in restoring the pure teachings of monotheism. These efforts are to refute liberalism and pluralism, forbid Christmas greetings, and rectify the purpose of the grave pilgrimage.